Development of an App to look up the anesthetic implications of genetic syndromes and rare diseases in patients. - Echeverry-Marín, Piedad C.; Pérez-Pradilla, Andrea C.; Jackeline Suárez, Layla; Cendales, Leonardo; Vivas, Juan P.; Santander, Carlo (Colombian Journal of Anesthesiology / Revista Colombiana de Anestesiología)
Introduction: Orphan diseases are a heterogeneous group of conditions involving the structure and functioning of several organs and systems; this represents a significant challenge for the anesthesiologist and the surgical team. Specific knowledge of each disease reduces the risk of any adverse events secondary to perioperative management errors in these patients. Objective: Developing a strategy to quickly and effectively look up for the perioperative risks of patients with rare diseases. Methods: An academic literature review was conducted and the information available in databases was selected. A group of engineers and designers summarized the information and developed a software application for mobile devices, to look up at a list of rare diseases, their description, any surgical implications, and the most relevant anesthetic considerations. Results: The CARAN App (CARAN is the Spanish acronym for Rare Cases in Anesthesia) was developed, which may be downloaded into any iOS (Apple) and Android mobile device at no cost. The App makes available information on the major anesthetic implications, with a view to improving patient care safety. This article discusses the first part of the project which comprises the development and design of the App and the review of 60 diseases. Additional diseases are expected to be included in the second phase of the project. Conclusion: We are introducing the first App available in Spanish to quickly and effectively look up for the most relevant anesthetic implications in 60 rare diseases.